Renal Impairment in Cirrhosis Unrelated to Hepatorenal Syndrome - Gavin Low; Graeme JM Alexander; David J Lomas (Canadian Journal of Gastroenterology and Hepatology)
Renal impairment is common in liver disease and may occur as a consequence of the pathophysiological changes that underpin cirrhosis or secondary to a pre-existing unrelated insult. Nevertheless, the onset of renal impairment often portends a worsening prognosis. Hepatorenal syndrome remains one of the most recognized and reported causes of renal impairment in cirrhosis. However, other causes of renal impairment occur and can be classified into prerenal, intrinsic or postrenal, which are the subjects of the present review.